Surface related differences between uncoated versus carbon-coated silicon nanowire electrodes on performance in lithium ion batteries - Krause, Andreas; Langklotz, Ulrike; Pohl, Diana; Tkacheva, Olga; Pohl, Darius; Nielsch, Kornelius; Mikolajick, Thomas; Weber, Walter M. (Journal of Energy Storage, 2020)
We present electrode assemblies of Si nanowires (NW) partially coated with a highly conductive nano-graphitic carbon layer. The surface modifications and overall electrode performance of these electrodes are investigated at high charge and discharge rates. The possibility to directly compare carbon-coated with uncoated SiNW electrodes allows to systematically separate the influences of Si and C on the battery performance and stability from a typically mixed system in electrodes. Consequently, a nanometer thin carbon layer is found to be efficient in withstanding mechanical stress and cracking during battery cycling. Moreover, the protective layer reduces the surface reactivity towards the electrolyte and enhances the electrode conductivity. On the other hand, we conclude that thicker carbon coatings reduce the performance of the Si nanowire network at high currents by introducing an additional diffusion barrier for Li ions.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Conductive carbon coating; High capacity; Lithium ion batteries; Scanning electron microscopy; Silicon nanowires; Surface properties